2012
DOI: 10.1021/jm301625s
|View full text |Cite
|
Sign up to set email alerts
|

Sulfocoumarins (1,2-Benzoxathiine-2,2-dioxides): A Class of Potent and Isoform-Selective Inhibitors of Tumor-Associated Carbonic Anhydrases

Abstract: Coumarins were recently shown to constitute a novel class of mechanism-based carbonic anhydrase (CA, EC 4.2.1.1) inhibitors. We demonstrate that sulfocoumarins (1,2-benzoxathiine 2,2-dioxides) possess a similar mechanism of action, acting as effective CA inhibitors. The sulfocoumarins were hydrolyzed by the esterase CA activity to 2-hydroxyphenyl-vinylsulfonic acids, which thereafter bind to the enzyme in a region rarely occupied by other classes of inhibitors. The X-ray structure of one of these compounds in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
138
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(143 citation statements)
references
References 48 publications
(106 reference statements)
2
138
0
Order By: Relevance
“…26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type. [55][56][57][58]60 Many such enzymes also possess biotechnologic applications for biomimetic CO 2 capture processes.…”
mentioning
confidence: 99%
“…26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type. [55][56][57][58]60 Many such enzymes also possess biotechnologic applications for biomimetic CO 2 capture processes.…”
mentioning
confidence: 99%
“…Found: C,50.27;H,4.14;N,14.44. General procedure for the preparation of: N,N-Dimethyl-4-(1-(2-(2-oxo-2H-chromene-3-carbonyl)hydrazono)ethyl)-benzenesulfonamide (17) and N,N-dimethyl-4-(1-(2-(3-oxo-3H-benzo[f]-chromene-2-carbonyl)hydrazono)ethyl)-benzenesulfonamide (18): Equimolecular mixture of 3 (3.08 g, 0.01 mol) and either salicaldehyde (1.22 g, 0.01 mol) or 2-hydroxy-1-naphthaldehyde (1.72 g, 0.01 mol) in dioxane (20 mL) containing piperidine (0.5 mL) was refluxed for 3h. The reaction mixture was poured onto ice/water and the obtained solid was recrystallized from dioxane containing few drops of HCl to give 17 or 18, respectively.…”
Section: Chemistrymentioning
confidence: 99%
“…It has also been well reported that sulfonamide bearing molecules act as promising anticancer agents through inhibition of carbonic anhydrase IX 11 . Crystallographic data revealed that CA IX, which is a membrane-associated a-CA, is comprised of a dimer each monomer of which consists of 10-stranded antiparallel-sheets forming the core of the molecule with an intramolecular disulfide bond between Cys23 and Cys203 11,18 . CA IX active site contains a Zn(II) in coordination with His94, 96, 119 and a water molecule.…”
Section: Molecular Modeling and Dockingmentioning
confidence: 99%
See 2 more Smart Citations